Reformas borbónicas, patronato real y la Inquisición en el Perú: la Relación del auto de fe de Pedro de Peralta Barnuevo (1733). - Rohner, Stephanie (Colonial Latin American Review, 2021)
The article focuses on fathoms the implications of this Peruvian polymath's takedown of the Holy Office in the service of Viceroy Castelfuerte and Bourbon reform project was still young. It mentions attempt to strengthen the authority of the viceroy on the inquisition embodied in Peralta's text and began to limit the privileges of the Church and its institutions. It also mentions viceroy allowed him to demonstrate that the Creole intellectuals.